PENGARUH PEMBIASAAN SHALAT DHUHA TERHADAP KEDISIPLINAN BELAJAR SISWA DI MIN 2 KOTA PALANGKA RAYA - Kevin Ramadhani Pratama; Istiyati Mahmudah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to explore the effect of dhuha prayer habituation on studentlearning discipline at MIN 2 Palangka Raya City. Dhuha prayer, as a sunnah worshipperformed in the morning, has become part of the school routine which is expectedto shape students' disciplinary character in terms of punctuality, responsibility, andconsistency in learning. This type of research is qualitative using observation,interview, and documentation study approaches. Data were collected through directobservation of the implementation of dhuha prayer and student learning behavior,interviews with teachers and students, and document analysis related to schoolpolicies regarding worship habituation. The results showed that the habituation ofdhuha prayer has a significant influence on student discipline. Students whoroutinely perform dhuha prayer tend to show improvement in terms of on-timeattendance, consistent completion of school assignments, and increased focusduring the learning process. The conclusion of this study is that the habituation ofdhuha prayer at MIN 2 Palangka Raya City can be one of the effective methods inimproving student learning discipline, as well as forming religious and responsiblecharacters